2020
DOI: 10.3390/pharmaceutics12080754
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mannose-Modified Carboxylated Curdlan-Coated Liposomes for Antigen Presenting Cell Targeted Antigen Delivery

Abstract: Specific delivery to antigen presenting cells (APC) and precise control of the intracellular fate of antigens are crucial to induce cellular immunity that directly and specifically attacks cancer cells. We previously achieved cytoplasmic delivery of antigen and activation of APC using carboxylated curdlan-modified liposomes, which led to the induction of cellular immunity in vivo. APCs express mannose receptors on their surface to recognize pathogen specifically and promote cross-presentation of antigen. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…At the same time, liposome as the drug carrier appears frequently in clinical treatment in recent years, which means that it has advantageous clinical transformed potentiality (31,32). The pair of mannose and mannose receptors can recognize and capture antigen molecules, promote antigen presentation, and regulate the maturation and differentiation of immune cells (33)(34)(35). Thus, we prepared mannose-modified liposomes to encourage the combination with APCs and stimulate maturation so as to activate the specific immunity of the body.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, liposome as the drug carrier appears frequently in clinical treatment in recent years, which means that it has advantageous clinical transformed potentiality (31,32). The pair of mannose and mannose receptors can recognize and capture antigen molecules, promote antigen presentation, and regulate the maturation and differentiation of immune cells (33)(34)(35). Thus, we prepared mannose-modified liposomes to encourage the combination with APCs and stimulate maturation so as to activate the specific immunity of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Once antigens have more opportunities to be captured, processed, and presented by APCs, stronger immune response would be induced. , To enhance the internalization of NPs by APCs, different ligands were used to modify the surface of NPs. Owing to the high expression of mannose receptors on APCs, mannose is commonly used for the surface modification of nanocarriers. , Therefore, we modified the CS-G@M with mannose, which could specifically recognize the mannose receptor on teleost APCs. By flow cytometry, we found that, compared with CS-G@M without mannose modification, CS-G@M-M showed significantly enhanced cellular uptake by macrophages (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the high expression of mannose receptors on APCs, mannose is commonly used for the surface modification of nanocarriers. 37,38 Therefore, we modified the CS-G@M with mannose, which could specifically recognize the mannose receptor on teleost APCs. By flow cytometry, we found that, compared with CS-G@M without mannose modification, CS-G@M-M showed significantly enhanced cellular uptake by macrophages (Figure 2A,B).…”
Section: Resultsmentioning
confidence: 99%
“…To improve cross-presentation efficiency, mannose residues were introduced into carboxylated polysaccharide derivatives to promote their uptake selectivity to APCs and mannose receptor (MR)-mediated cross-presentation. 25 The mannose residue introduction increased the uptake selectivity considerably, but cross-presentation efficiency was not so improved, probably because the introduction of mannose residue into polysaccharide derivatives might have decreased the cytosolic delivery performance. 25…”
Section: Introductionmentioning
confidence: 99%
“…25 The mannose residue introduction increased the uptake selectivity considerably, but cross-presentation efficiency was not so improved, probably because the introduction of mannose residue into polysaccharide derivatives might have decreased the cytosolic delivery performance. 25…”
Section: Introductionmentioning
confidence: 99%